2012
DOI: 10.1016/j.jmaa.2012.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation for turbulent flows with critical regularization

Abstract: In this paper, we establish the existence of a unique "regular" weak solution to the Large Eddy Simulation (LES) models of turbulence with critical regularization. We first consider the critical LES for the Navier-Stokes equations and we show that its solution converges to a solution of the Navier-Stokes equations as the averaging radii converge to zero. Then we extend the study to the critical LES for Magnetohydrodynamics equations. MSC: 35Q30, 35Q35, 76F60

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…For this reason one can replace the classical Laplace operator by the Laplace operator with fractional regularization θ and seek for the limiting case where we can prove global existence and uniqueness of regular solutions. In a series of papers [10,4,1,2], it was shown that the LES models which are derived by using instead of the operator (1.1), the operator A θ = I + α 2θ (−∆) θ for suitable (large enough) θ < 1, are still well-posed. In this paper, we consider LES models with fractional filter acting only in one variable…”
Section: Introduction and Notationmentioning
confidence: 99%
“…For this reason one can replace the classical Laplace operator by the Laplace operator with fractional regularization θ and seek for the limiting case where we can prove global existence and uniqueness of regular solutions. In a series of papers [10,4,1,2], it was shown that the LES models which are derived by using instead of the operator (1.1), the operator A θ = I + α 2θ (−∆) θ for suitable (large enough) θ < 1, are still well-posed. In this paper, we consider LES models with fractional filter acting only in one variable…”
Section: Introduction and Notationmentioning
confidence: 99%
“…Proof of Theorem 4.1. The proof of Theorem 4.1 follows the lines of the proof of the Theorem 4.1 in [5], that we have to modify in order to treat the cases when θ ≤ 3 4 . Thus we will use [5] as a reference and only point out the differences between their proof of convergence to the mean Navier-Stokes equations and the proof of convergence in the present study.…”
Section: Limit When N → ∞mentioning
confidence: 99%
“…For θ > 3 4 , Berselli and Lewandowski [5] showed the convergence of the ADM solution, with fractional regularization, to a solution of the average Navier-Stokes Equations when N goes to infinity. The existence and the uniqueness of a solution to this model in the case N = 0 and θ ≥ 1 6 are studied in [3].…”
Section: Introductionmentioning
confidence: 99%